The Role of Health Cadres Significantly Influences Elderly Participation in the Elderly Integrated Health Service Post - Riada Mareny Pasaribu; Eka SR Sihombing; Karolina Karolina; Yeci Theresia Simanjuntak; Mei Linawati Siahaan (FORIKES, 2026)
The Elderly Integrated Health Service Post functions as an early detection program for health problems among older adults. Attendance of elderly individuals at this service is influenced by several factors, one of which is the role of health cadres. Cadres act as community mobilizers, provide health education, and monitor elderly health conditions. This study aims to determine the relationship between the role of health cadres and the attendance of elderly individuals in the Elderly Integrated Health Service Post at the working area of Raya Health Center, Teladan Subdistrict, Pematangsiantar City. A cross-sectional design was employed. The population consisted of 375 elderly individuals aged 60–80 years. A sample of 94 respondents was selected using systematic random sampling. Data were collected through questionnaires and analyzed using Spearman’s Rho test. The hypothesis test yielded a p-value of 0.000, indicating a significant relationship between the role of health cadres and the activeness of elderly individuals in attending the Elderly Integrated Health Service Post in Teladan Subdistrict, Pematangsiantar City. In conclusion, the findings demonstrate that the role of health cadres significantly influences elderly participation in the Elderly Integrated Health Service Post. Strengthening cadre involvement may enhance elderly attendance and improve early detection of health problems.Keywords: Elderly Integrated Health Service Post; health cadres; elderly attendance